When Suits Meet Roots: The Antecedents and Consequences of Community Engagement Strategy - Bowen, Frances (Journal of business ethics, 2010)
Understanding firms’ interfaces with the community has become a familiar strategic concern for both firms and non-profit organizations. However, it is still not clear when different community engagement strategies are appropriate or how such strategies might benefit the firm and community. In this review, we examine when, how and why firms benefit from community engagement strategies through a systematic review of over 200 academic and practitioner knowledge sources on the antecedents and consequences of community engagement strategy. We analytically describe evidence on the rise of the community engagement strategy literature over time, its geographical spread and methodological evolution. A foundational concept underlying many studies is the ‘continuum of community engagement’. We build on this continuum to develop a typology of three engagement strategies: transactional, transitional and transformational engagement. By identifying the antecedents and outcomes of the three strategies, we find that the payoffs from engagement are largely longer-term enhanced firm legitimacy, rather than immediate cost–benefit improvements. We use our systematic review to draw implications for future research and managerial practice.